Phytoremediation of Cadmium-, Lead-, and Nickel-Polluted Soils by Industrial Hemp - Giorgio Testa; Sebastiano Andrea Corinzia; Salvatore Luciano Cosentino; Barbara Rachele Ciaramella (Agronomy, 2023)
The restoration of polluted soils is crucial for ecosystem recovery services. Evidently, phytoremediation is a biological and sustainable technique that includes the use of plants to remediate heavy-metal-contaminated land; the plants should be tolerant to the contamination and capable of uptake or immobilization of the heavy metals in the soil. Moreover, defining an economically efficient approach to the remediation of a contaminated area, with the possibility of further utilization of phytoremediation biomass, renders energy crops a great option for this technique. Energy crops, in fact, are known for their ability to grow with low agricultural input, and later, the biomass product can be used to produce biofuels, bioenergy, and bioproducts in a sustainable and renewable way, creating economic potential, especially when these crops are cultivated in marginal lands. The aim of this work is to test two monoecious industrial hemp varieties in different levels of Cd, Pb, and Ni in soil. Both varieties were tolerant to levels of Cd and Pb contamination that were higher than the limit for commercial and industrial use, while Ni showed a significant effect at all the tested concentrations. The variety Futura 75 performed better than Kc Dora in terms of productivity and tolerance.